Lung Metastasis after an Eighteen-Years-Long Disease-Free Period since Uterine Leiomyosarcoma Diagnosis. (12th March 2014) - Guazzaroni, M.; Tosti, D.; Rascioni, M.; Mataloni, M.; Citraro, D.; Simonetti, G.
Abstract : Uterine leiomyosarcoma (ULMS) is an uncommon malignancy that accounts for one-third of uterine sarcomas and represents 1% of all uterine malignancies, with an incidence averaging 0.5–1/100, 000/year. The prognosis is poor due to its intrinsic aggressiveness and its characteristic high metastatic potential with reported distant metastatic spread in lung, abdomen, soft tissue, and brain. We present the case of a 67-year-old woman with lung metastasis after eighteen years since uterine leiomyosarcoma diagnosis and its following surgical resection. The diagnosis of pulmonary metastases was obtained by reviewing the histology of the previous uterine tumor: the tumor cells were immunoreactive for CD10, PR, and smooth muscle actin (SMA), but negative for desmin, S100, CD34, CD 117, cytokeratins AE1AE3, CD68R, and ER. To our knowledge, this disease-free interval is the longest among previous reports of pulmonary metastasis of uterine leiomyosarcoma.